Reinnervation of striated muscle by peripheral vagal fibres cut above or below the nodose ganglion in the cat and rabbit. - Coget, J (1983)
In cats and rabbits, the peripheral stump of the vagus nerve cut above the nodose ganglion (supranodose anastomoses: s.n.) or below this ganglion (infranodose anastomoses: i.n.) was either sutured with epineurial sutures to the peripheral stump of the branch of the spinal accessory motor nerve innervating the sterno-cleido-mastoid (s.c.m.) muscle, or directly implanted in this muscle after resection of its motor nerve. After about six months, reinnervation of this muscle by vagal fibres was studied. By electromyographic recording during electrical stimulation of the cervical vagus nerve, it was shown that the vagal reinnervation of the s.c.m. muscle was established in 65% of the cats studied (57% s.n., 69% i.n.) and 33% of rabbits (37% s.n. and 31% i.n.). The average number of distinct potentials recorded in the reinnervated muscle, following vagal stimulation, was twenty-two in s.n. cats, thirteen in i.n. cats, eleven in s.n. rabbits and twelve in i.n. rabbits. Recorded potentials were monophasic (8%), biphasic (22.5%), triphasic (11.5%) or polyphasic (58%). These potentials were abolished by curare and alpha-bungarotoxin. The use of retrograde axonal transport of horseradish peroxidase showed labelled cells in the nodose ganglion, the cervical vagus and cranial thoracic vagus, and in the stellate ganglia. It is concluded that cholinergic vagal afferents reinnervated the s.c.m. muscle. Involvement of the sympathetic system is discussed.